Răspuns :
a : b = 6 rest 33 ⇒ a = 6 x b + 33
a - b = 628
6×b + 33 - b = 628
5×b = 628 - 33
5×b= 595
b = 595 : 5
b = 119
a = 6×119 + 33 =714 + 33 = 747
c = d × 4 - 19
c + d = 401
4×d - 19 + d = 401
5×d = 401 + 19
5×d = 420
d = 420 : 5
d = 84
c= 401 - 84 =317
e = a + b
e = a+b = 747 + 119 = 866
a - b = 628
6×b + 33 - b = 628
5×b = 628 - 33
5×b= 595
b = 595 : 5
b = 119
a = 6×119 + 33 =714 + 33 = 747
c = d × 4 - 19
c + d = 401
4×d - 19 + d = 401
5×d = 401 + 19
5×d = 420
d = 420 : 5
d = 84
c= 401 - 84 =317
e = a + b
e = a+b = 747 + 119 = 866
a : b = 6 rest 33
a = 6×b+33 (conform teoremei mipartirii cu rest)
a - b = 628
inlocuim pe "a" cu 6×b+33
6×b+33 - b = 628
5×b = 628 - 33
5×b = 595
b = 595 : 5
b = 119
a = 628 + 119 = 747
c + d = 401
c = 4 × d - 19
==> 4 × d - 19 + d = 401
==> 5 × d = 401 + 19
==> 5 × d = 420
==> d = 420 : 5
==> d = 84
c = 401 - 84 = 317
e = a + b = 747 + 119 = 866
a = 747
b = 119
c = 317
d = 84
e = 866
a = 6×b+33 (conform teoremei mipartirii cu rest)
a - b = 628
inlocuim pe "a" cu 6×b+33
6×b+33 - b = 628
5×b = 628 - 33
5×b = 595
b = 595 : 5
b = 119
a = 628 + 119 = 747
c + d = 401
c = 4 × d - 19
==> 4 × d - 19 + d = 401
==> 5 × d = 401 + 19
==> 5 × d = 420
==> d = 420 : 5
==> d = 84
c = 401 - 84 = 317
e = a + b = 747 + 119 = 866
a = 747
b = 119
c = 317
d = 84
e = 866